Proyecto de factibilidad para la creación de una empresa de turismo ecológico para personas de la tercera edad en la ciudad de Quito - Romero Soria, Nelson Fabián (2014)
This project relates to the feasibility of creating an eco-tourism company for elderly people in the city of Quito. This study will help to determine the feasibility of implementing the project. In the present study the analysis and justification of the project which is aimed at older people was conducted by providing services according to their needs. The research problem is presented through a diagnosis of the current situation, as are the limitations of the older people to perform different activities. They comprise the objectives, using them is determined, starting a business eco-tourism in the city of Quito.